In2S3-based saturable absorber for passively harmonic mode-locking in 2 μm region. (January 2022) - Ma, Xiaohui; Chen, Wu; Tong, Liang; Liu, Shaoqing; Dai, Wenwen; Ye, Shanshan; Zheng, Ziqi; Wang, Yangyang; Zhou, Yong; Zhang, Wei; Fang, Wentan; Chen, Xiaolin; et al.
Highlights: The mode-locking function of In2 S3 was experimentally demonstrated for the first time. The 2nd to 11st harmonics were realized in 2-μm region. The maximum harmonic-resonance frequency of 459 MHz that has ever been demonstrated in a In2 S3 -based fiber laser. Abstract: There are few reports on the mode-locking operation of indium sulfide (In2 S3 ) in fiber lasers. In this paper, we experimentally demonstrate a harmonic mode-locked fiber laser in 2-μm region by taking advantage of an In2 S3 -based saturable absorber (SA). The In2 S3 -based SA has nonlinear optical modulation depth of 20.8 % and saturation power of 0.14 kW at 1930 nm. The fundamentally mode-locked solitons at 1938.59 nm with the 3-dB bandwidth of 5.04 nm, pulse width of 1.16 ps, and pulse repetition rate of 41.73 MHz are generated. The maximum harmonic-resonance frequency is 459 MHz (11th harmonic), which is the highest operating frequency that has been demonstrated in In2 S3 -based mode-locked fiber lasers as far as we know. The spectral and temporal characteristics of the output pulses are investigated versus harmonic order. The results prove that In2 S3 possesses the characteristics of mode-lockers and could be a promising optical switch for ultrafast pulses generation.